Tribody [(HER2)2xCD16] Is More Effective Than Trastuzumab in Enhancing γδ T Cell and Natural Killer Cell Cytotoxicity Against HER2-Expressing Cancer Cells - Oberg, Hans H.; Kellner, Christian; Gonnermann, Daniel; Sebens, Susanne; Bauerschlag, Dirk; Gramatzki, Martin; Kabelitz, Dieter; Peipp, Matthias; Wesch, Daniela (Frontiers in Immunology, 2018)
An enhanced expression of human epidermal growth factor receptor 2 (HER2, ErbB2) often occurs in an advanced stage of breast, ovarian, gastric or esophageal cancer and pancreatic ductal adenocarcinoma (PDAC). Commonly, HER2 expression is associated with poor clinical outcome or chemoresistance in ovarian and breast cancer patients. Treatment with humanized anti-HER2 monoclonal antibodies such as trastuzumab or pertuzumab has improved the outcome of patients with HER2-positive-metastatic gastric or breast cancer, but not all patients benefit. In this study, the bispecific antibody [(HER2)2xCD16] in the tribody format was employed to re-direct CD16-expressing γδ T lymphocytes as well as natural killer (NK) cells to the tumor-associated cell surface antigen HER2 to enhance their cytotoxic anti-tumor activity. Tribody [(HER2)2xCD16] comprises two HER2-specific single chain fragment variable (scFv) fused to a fragment antigen binding (Fab) directed to the CD16 (FcγRIII) antigen expressed on γδ T cells and NK cells. Our results revealed the superiority of tribody [(HER2)2xCD16] compared to trastuzumab in triggering γδ T cell and NK cell-mediated lysis of HER2-expressing tumor cells such as PDAC, breast cancer and autologous primary ovarian tumors. The increased efficacy of [(HER2)2xCD16] can be explained by an enhanced degranulation of immune cells. Although CD16 expression was decreased on γδ T cells in several PDAC patients and the number of tumor-infiltrating NK- and γδ T cells was impaired in ovarian cancer patients, [(HER2)2xCD16] selectively enhanced cytotoxicity of cells from these patients. Here, unique anti-tumor properties of tribody [(HER2)2xCD16] are identified which beyond addressing HER2 overexpressing solid tumors may allow to treat with similar immunoconstructs combined with the adoptive transfer of γδ T cells and NK cells refractory hematological malignancies. A major advantage of γδ T cells and NK cells in the transplant situation of refractory hematological malignancies is given by their HLA-independent killing and a reduced graft-versus-host disease.